Photocatalytic hydrogenation of acetophenone on a titanium dioxide cellulose film. Issue 12 (1st March 2022) - Thiel, Tabea A.; Obata, Keisuke; Abdi, Fatwa F.; van de Krol, Roel; Schomäcker, Reinhard; Schwarze, Michael
Abstract : The photocatalytic hydrogenation of acetophenone to 1-phenylenthanol was investigated with cellulose-immobilized titanium oxide (TiO2 ) particles. Abstract : A previously developed sustainable immobilization concept for photocatalysts based on cellulose as a renewable support material was applied for the photocatalytic hydrogenation of acetophenone (ACP) to 1-phenyl ethanol (PE). Four different TiO2 modifications (P25, P90, PC105, and PC500) were screened for the reaction showing good performance for PC25 and PC500. PC500 was selected for a detailed kinetic study to find the optimal operating conditions, and to obtain a better understanding of the photocatalytic pathway in relation to conventional and transfer hydrogenation. The kinetic data were analyzed using the pseudo-first-order reaction rate law. A complete conversion was obtained for ACP concentrations below 1 mM using a 360 nm filter and argon as the purge gas within 2–3 hours. High oxygen concentrations slow down or prevent the reaction, and wavelengths below 300 nm lead to side-products. By investigating the temperature dependency, an activation energy of 22 kJ mol −1 was determined which is lower than the activation energies for conventional and transfer hydrogenation, because the light activation of the photocatalyst turns the endothermic to an exothermic reaction. PC500 was immobilized onto the cellulose film showing a 37% lower activity that remains almost constant after multiple use.